Professional Xen virtualization - Von Hagen, William (Wrox professional guides., 2008)
Covers the aspects of virtualization on the Linux platform for administrators seeking to optimize the use of enterprise hardware, create virtual environments, or establish a testing environment. This book provides a foundation in virtualization, XEN, and competing approaches using discussions of installing, configuring, and using XEN.